Representation of the Concept of Time and Destiny: Metaphorical Analysis in the Poem Da’i al-Ayyāma Taf’alu Mā Tashā’u by Imam Syafi’i - Harisa, Jihan; Dhiya’ah, Harirotudh; Auliya , Syifa (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study aims to examine the use of metaphors in Imam Shafi’i’s poem Da’i al-Ayyāma Taf’alu Mā Tashā’u and to uncover the meanings that reflect the concepts of time and destiny contained within it. This study employs a qualitative method with a stylistic approach. The data, consisting of the poem’s text, was analyzed through in-depth reading, note-taking, and the categorization of metaphor types based on stylistic analysis. The analysis process involved identifying metaphorical forms, classifying them into specific categories, and then interpreting their meanings in relation to moral and religious messages. The results of the study indicate that the metaphors used in these poems include conceptual and symbolic metaphors that represent time as a constantly moving force and life as a process of change. Furthermore, metaphors also play a role in instilling the values of patience and an attitude of tawakal (trust in God’s will) toward destiny. Thus, the metaphors in these poems serve not only as aesthetic elements but also as a means of conveying spiritual and philosophical values regarding human life.